2020
DOI: 10.1080/07294360.2020.1830039
|View full text |Cite
|
Sign up to set email alerts
|

Students’ views about the purpose of higher education: a comparative analysis of six European countries

Abstract: Across Europe, assumptions are often made within the academic literature and by some social commentators that students have come to understand the purpose of higher education (HE) in increasingly instrumental terms. This is often linked to processes of marketisation and neo-liberalisation across the Global North, in which the value of HE has come to be associated with economic reward and labour market participation and measured through a relatively narrow range of metrics. It is also associated with the establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 17 publications
3
19
2
1
Order By: Relevance
“…28.71% ( n = 29) of questionnaire respondents ‘agreed strongly’ and 35.64% ( n = 36) ‘agreed somewhat’ that they ‘chose/choose modules based on whether they will help [their] future career’. These findings are concurrent with Brooks et al ( 2021 ) whose research with students found that the most common purpose of HE was to prepare themselves for the labour market. This supports the view of student consumerism which positions the student-consumer as focused on gaining access to a financially rewarding career (Bossick 2009 ).…”
Section: Findings and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…28.71% ( n = 29) of questionnaire respondents ‘agreed strongly’ and 35.64% ( n = 36) ‘agreed somewhat’ that they ‘chose/choose modules based on whether they will help [their] future career’. These findings are concurrent with Brooks et al ( 2021 ) whose research with students found that the most common purpose of HE was to prepare themselves for the labour market. This supports the view of student consumerism which positions the student-consumer as focused on gaining access to a financially rewarding career (Bossick 2009 ).…”
Section: Findings and Discussionsupporting
confidence: 83%
“…Whether students identify as, behave like, or navigate through HE as a ‘consumer’ remains a ‘contested yet under-analysed entity’ (Nixon et al 2016 , p. 1). As Brooks et al ( 2021 ) assert, claims that students have become consumer-like in their behaviour are often made based on limited empirical evidence, rather than exploring the perspective of students themselves. This research therefore helps to address this gap in the literature and contributes to a growing body of empirical work to emerge over the last 5 years which engages with the changing identities of students in a marketised British higher education sector (Tomlinson 2017 ; Budd 2016 ; Bunce et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Those results are, to some extent, consistent with research conducted by Svabova and Kramarova (2021). However, another recent study of European students indicates the importance of tertiary education for personal and societal growth and development rather than economic gains (Brooks et al. , 2021).…”
Section: Related Literaturesupporting
confidence: 88%
“…Iako bi se, na prvi pogled, moglo pretpostaviti da je pomjeranje granica poznatog neophodan element za usavršavanje, te da, hipotetičkom povratnom spregom, ono pozitivno utiče na privredu, ovakvo posmatranje je u velikoj mjeri zabluda, budući da je pomenuta povratna sprega zasnovana upravo na ideologiji koja definiše način evaluacije uspjeha institucija kroz njihovo ekonomsko djelovanje. Drugim riječima, vrijednost institucije se, društveno gledano, određuje na osnovu njenog ekonomskog učinka, iskazanog kroz njen finansijski potencijal, pa na osnovu ovoga postaje jasnije i da se, posmatrano unutar ove ideološke kutije, saznanje kao cilj vrednuje daleko manje u odnosu na jednostavnu obuku radnika za struku (Brooks, Gupta, Jayadeva, & Abrahams, 2020), te da ovakav vid implementacije akademije, bez obzira na finansijsku jačinu sprege sa privredom, koja je tipično relativno slaba (National Science Board, 2018) (OECD (2021), 2021) (Atkinson & Foote, 2019), na nju ne djeluje nužno pozitivno (Bloch & Sørensen, 2015) (Jacob & Lefgren, 2011) (Larson, Ghaffarzadegan, & Diaz, 2012) (Bauwens Luc, 2011 (Gök, Rigby, & Shapira, 2016) (Archer, 2020). Naravno, stvarni problem je ovdje sakriven, jer je implicitna sugestija da se svojevrsnom "Ptolomizacijom" (Žižek, 2019) može doći do ispravnog rješenja, dok stvarno rješenje podrazumijeva promjenu osnovne perspektive na problem.…”
Section: Destruktivni Uticaj Posthumanističke Semiotičke Ideologije N...unclassified